A terahertz Brewster switch based on superconductor hyperbolic metamaterial - Sreekanth, Kandammathe Valiyaveedu (2021)
Active polarization switching devices are important to control the polarization state of light including terahertz (THz) waves that are technologically challenging to manipulate. Here, we propose and numerically demonstrate a hyperbolic metamaterial-based (HMM-based) active Brewster polarization switch for the intensity and phase modulation of THz light. The proposed multilayered HMM consists of alternating thin layers of high temperature superconductors such as yttrium barium copper oxide and dielectric materials such as lanthanum aluminate. The HMM shows elliptical dispersion above the superconducting phase transition temperature and type II hyperbolic dispersion in the superconducting state. By varying the temperature from the dielectric to the superconducting phase of the HMM, we demonstrate above 98% THz intensity modulation and 100% phase tunability (180°) at Brewster’s angle. The proposed HMM can work as an efficient reflective THz modulator by properly selecting the angle of incidence.